Pengaruh Literasi Keuangan Dan Financial Technnology Terhadap Keberlangsungan Usaha Pelaku Umkm Di Kabupaten Banyumas - Rahmania Mustahida; Eka Yuliyanti; Anisa Kusumawardani; Zati Fadilla (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2024)
The purpose of this study was to determine the factors that influence business continuity in Banyumas Regency MSMEs. The data in this study were collected by conducting a questionnaire survey on 99 Banyumas Regency MSME businesses to analyze the role of financial literacy and financial technology variables in business continuity. The data collection technique used a simple random sampling technique with the Slovin formula to obtain a sample of 99 Banyumas Regency MSME business actors. The results of the study state that financial literacy has a positive and significant effect on business continuity, financial technology has a positive and significant effect on business continuity. The Coefficient of Determination test states that the independent variable is able to influence business continuity by 23.2% while the remaining 76.8% is influenced by other variables outside the study.